2021
DOI: 10.1186/s41232-021-00175-6
|View full text |Cite
|
Sign up to set email alerts
|

The role of lymphatics in intestinal inflammation

Abstract: The lymphatic vasculature returns filtered interstitial arterial fluid and tissue metabolites to the blood circulation. It also plays a major role in lipid absorption and immune cell trafficking. Lymphatic vascular defects have been revealed in inflammatory diseases, Crohn’s disease, obesity, cardiovascular disease, hypertension, atherosclerosis, and Alzheimer’s disease. In this review, we discuss lymphatic structure and function within the gut, such as dietary lipid absorption, the transport of antigens and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 70 publications
0
15
0
Order By: Relevance
“…To characterize the transcriptional profile of CD4 + T cells under gut inflammation conditions, we isolate conventional CD4 + T cells (CD4 + TCRb + GFP - ) from colonic lamina propria. Despite mesenteric lymph nodes, which drain the colonic tissue, might be considered a proper control to compare what is happening in the lamina propria 31 , we chose splenic CD4 + T cells as a control since our previous studies have shown a similar profile between T cells isolated from colonic lamina propria and mesenteric lymph nodes, but different from those isolated from the spleen upon gut inflammation 14 , 32 . Then, we performed bulk RNA sequencing on these samples, and then compared the inflamed condition with the control.…”
Section: Resultsmentioning
confidence: 99%
“…To characterize the transcriptional profile of CD4 + T cells under gut inflammation conditions, we isolate conventional CD4 + T cells (CD4 + TCRb + GFP - ) from colonic lamina propria. Despite mesenteric lymph nodes, which drain the colonic tissue, might be considered a proper control to compare what is happening in the lamina propria 31 , we chose splenic CD4 + T cells as a control since our previous studies have shown a similar profile between T cells isolated from colonic lamina propria and mesenteric lymph nodes, but different from those isolated from the spleen upon gut inflammation 14 , 32 . Then, we performed bulk RNA sequencing on these samples, and then compared the inflamed condition with the control.…”
Section: Resultsmentioning
confidence: 99%
“…In addition to returning fluid to the blood vasculature, lymphatics are the primary transporter of lipid and lipid-soluble substances (including lipid-soluble vitamins) from the intestine to the blood. The specific molecular methods that regulate uptake of chylomicrons into lacteals are not well understood, however it is known that this task cannot be completed through portal blood absorption [ 1 , 6 , 7 , 8 ].…”
Section: Overview Of the Intestinal Lymphatic Vasculaturementioning
confidence: 99%
“…Notably, lymphatic abnormalities have been increasingly recognized as contributing to the pathogenesis of IBD. Importantly, impaired lymphatic drainage due to dilation, obstruction, and dysfunction results in the accumulation of fluid and infiltrating immune cells, thus setting up chronic edema and inflammation [ 8 , 9 , 15 ]. In humans with IBD, increased lymphangiectasia, lymphadenopathy and lymphatic obstruction correlate with a poor prognosis.…”
Section: Pathophysiologymentioning
confidence: 99%
See 1 more Smart Citation
“…Particles or molecules in blood hold the possibility to enter LNs via high endothelial venules (HEVs), but this pathway may lead to a relatively low LN-targeting efficiency since substances in blood will have many ways to go or be captured [ 12 , 13 ]. On the other hand, a LN is “protected” by a fibrous capsule that is basically not permeable, and therefore reaching into LNs generally need to enter the lymphatics which have higher permeability [ 14 ], and then arrive LNs via the afferent lymphatic vessels. Particles entering lymphatics via a cell-free passive diffusion can be classified as the “passive transport”, while particles reaching into LNs by using cells ( e.g.…”
Section: Introductionmentioning
confidence: 99%